All Days 2015
DOI: 10.2118/174182-ms
|View full text |Cite
|
Sign up to set email alerts
|

40 Years of Low-Salinity Waterflooding in Pervomaiskoye Field, Russia: Incremental Oil

Abstract: Low-salinity waterflooding (LSW) and its effect on oil recovery factor have been studied around the world during the last 30 years. Low-salinity/fresh water was used in the initial stage of waterflooding because of deficiency of produced water. The Pervomaiskoye oil field in Republic of Tatarstan is one of the examples. Waterflooding started in 1966. Water was taken from the nearest water source, the Kama River. After more than 40 years, about two PVI has been injected, and 30.1% of this injected water was low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Little improvement in recovery was observed for both field cases because the low saline brine was injected below the water-oil contact. Meanwhile, Akhmetgareev and Khisamov [231] evaluated a historical injection of low saline water sourced from the nearest Karma river in the Pervomaiskoye oil field in the Republic of Tatarstan, Russia. They observed that more than one-third of the wells were not potentially effective, which is similar to conclusions made by Zeinijahromi et al [229].…”
Section: Sandstone Reservoirsmentioning
confidence: 99%
See 1 more Smart Citation
“…Little improvement in recovery was observed for both field cases because the low saline brine was injected below the water-oil contact. Meanwhile, Akhmetgareev and Khisamov [231] evaluated a historical injection of low saline water sourced from the nearest Karma river in the Pervomaiskoye oil field in the Republic of Tatarstan, Russia. They observed that more than one-third of the wells were not potentially effective, which is similar to conclusions made by Zeinijahromi et al [229].…”
Section: Sandstone Reservoirsmentioning
confidence: 99%
“…Then, Tang and Morrow [13] proposed that the crude oil adsorbed onto fines-coated rock surface is mobilized with the detachment of mixed-wet fines during low saline brine injection rendering the mineral more water-wet due to exposure of the water-wet surfaces beneath the detached fines (see Figure 8). Bedrikovetsky and his colleagues [70,74] developed an analytical model based on torques balance and mass balance to describe the relationship between the static equilibrium of clay particles and salinity, which was also used in the study by Akhmetgareev and Khisamov [231]. The torque balance is distorted when the detaching torque of drag and lifting forces exceeds the attaching torque of electrostatic and gravity forces, resulting in fines detachment and migration during the arrival of low saline brine.…”
Section: Swelling Of Clay and Fines Mobilizationmentioning
confidence: 99%
“…Little improvement in recovery was observed for both field cases because the low saline brine was injected below the water-oil contact. Meanwhile, Akhmetgareev and Khisamov [203] evaluated an historical injection of low saline water sourced from nearest Karma river in Pervomaiskoye oil field in Republic of Tatarstan, Russia. They observed that more than one-third of the wells was not potentially effective, which is similar to conclusions made by Zeinijahromi, et al [201].…”
Section: Sandstone Reservoirsmentioning
confidence: 99%
“…Then, Tang and Morrow [7] proposed that the crude oil adsorbed onto finescoated rock surface is mobilized with the detachment of mixed-wet fines during low saline brine injection rendering the mineral more water-wet due to exposure of the water-wet surfaces beneath the detached fines. Bedrikovetsky and colleagues [216,217] developed an analytical model based on torques balance and mass balance to describe the relationship between the static equilibrium of clay particles and salinity, which was also used in the study by Akhmetgareev and Khisamov [203]. The torque balance is distorted when the detaching torque of drag and lifting forces exceeds the attaching torque of electrostatic and gravity forces, resulting in fines detachment and migration during the arrival of low saline brine.…”
Section: Proposed Mechanisms In Sandstone Rocks: 411 Swelling Of CLmentioning
confidence: 99%
See 1 more Smart Citation